2009
DOI: 10.1083/jcb1853oia5
|View full text |Cite
|
Sign up to set email alerts
|

The activation-induced cytidine deaminase (AID) efficiently targets DNA in nucleosomes but only during transcription

Abstract: The activation-induced cytidine deaminase (AID) initiates somatic hypermutation, classswitch recombination, and gene conversion of immunoglobulin genes. In vitro, AID has been shown to target single-stranded DNA, relaxed double-stranded DNA, when transcribed, or supercoiled DNA. To simulate the in vivo situation more closely, we have introduced two copies of a nucleosome positioning sequence, MP2, into a supercoiled AID target plasmid to determine where around the positioned nucleosomes (in the vicinity of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Thus, the meaning of RNAPII accumulation across S regions may be distinct from its promoter-proximal pausing. Previous studies showed that, in the absence of transcription, nucleosomes prevented AIDmediated cytidine deamination (65), whereas with transcription, AID readily gained access to DNA in nucleosomes on both strands (65). Therefore, we propose that RNAPII pausing at S regions probably facilitates the repositioning of repressive nucleosomes to create a permissive chromatin architecture that allows AID to access target DNA sequences.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the meaning of RNAPII accumulation across S regions may be distinct from its promoter-proximal pausing. Previous studies showed that, in the absence of transcription, nucleosomes prevented AIDmediated cytidine deamination (65), whereas with transcription, AID readily gained access to DNA in nucleosomes on both strands (65). Therefore, we propose that RNAPII pausing at S regions probably facilitates the repositioning of repressive nucleosomes to create a permissive chromatin architecture that allows AID to access target DNA sequences.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the in vitro assay for DNA deamination by AID should be reexamined using mammalian Pol II and its cofactors on chromatin templates; previous studies have used naked DNA and T7 polymerase (9,35). It would also be important to examine how FACT and nucleosomes with H3K4me3 are influencing the DNA deamination reaction, and whether AID or uracil DNA glycosylase is preferentially recruited to chromatin with H3K4me3.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Recently, it was shown that in vitro nucleosomes prevent AID access, unless the immunoglobulin segment is being transcribed. 30 Transcription is required for SHM in vivo, presumably in part to loosen the contact of nucleosomes with the DNA. 31 During transcription, the single-stranded DNA (ssDNA) is prone to AID-mediated C to U conversion, producing U:G mismatches in the DNA.…”
Section: Discussionmentioning
confidence: 99%